FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN CASH HOLDING PADA PERUSAHAAN MANUFAKTUR - Lydia Meliana; Yuniarwati Yuniarwati (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research is to acknowledge the influence of firm size, liquidity, and the cash flow volatility of the firm itself against the manufacturing firm's cash holding that is listed in the Indonesia Stock Exchange (IDX) from the period of 2017-2019. There are a total of 87 manufacturing firm samples that are being collected for this purpose. Furthermore, a specific program called Econometric Views (Eviews version.11) is utilized to process the dataset. This research chooses to use fixed effect model (FEM) and multiple linear regression analysis. The result shows that firm size has a significant positive effect on corporate cash holding. Liquidity has a significant negative effect on corporate cash holding. Cash flow volatility has an insignificant effect on corporate cash holding.